Psychoactive drug use by medical students: a review of the national and international literature - Mesquita, Ana Maria; Laranjeira, Ronaldo; Dunn, John (São Paulo Medical Journal, 1997)
Non-medical drug use among medical students is a major concern among researchers and policy makers in several countries, not only because of the personal harmful consequences that may arise from this behavior, but also for the social consequences. This article aims to evaluate national and international data available on non-medical drug-use among medical students and risk factors associated with these problems, as well as social and institutional implications. Prevalence rates, in Brazilian and international samples, of alcohol and drug use, abuse and dependence, reasons for onset, methodological issues, and the role of medical education are presented, compared and discussed. The authors suggest some issues that should be a addressed in order to deal with this complex situation.